The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.18632/oncotarget.19547
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic/prognostic potential and molecular functions of long non-coding RNAs in the exosomes derived from the bile of human cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is an aggressive malignancy associated with unfavorable prognosis, and it’s difficult to diagnose and no effective treatments are available. Long non-coding RNAs (lncRNAs) play important roles in tumorigenesis and metastasis. Intact lncRNAs from exosomes have sparked much interest as potential biomarker for the non-invasive analysis of disease. Here, via exosome sequencing on lncRNAs, GO analysis, KEGG pathway and co-expression analysis, receiver operating characteristic curve and surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 31 publications
(31 reference statements)
2
51
0
1
Order By: Relevance
“…Our previous study showed differentially expressed lncRNAs in exosomes derived from bile of CCA patients . To investigate whether the indicated lncRNAs previously sequenced and verified in CCA bile exosomes were differentially expressed in CCA tissues, we first used qRT‐PCR to detect and compare the expression levels of 10 lncRNAs in CCA and adjacent tissues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study showed differentially expressed lncRNAs in exosomes derived from bile of CCA patients . To investigate whether the indicated lncRNAs previously sequenced and verified in CCA bile exosomes were differentially expressed in CCA tissues, we first used qRT‐PCR to detect and compare the expression levels of 10 lncRNAs in CCA and adjacent tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed differentially expressed lncRNAs in exosomes derived from bile of CCA patients. 8 To investigate whether the indicated lncRNAs previously sequenced and verified in CCA bile exosomes were differentially expressed in CCA tissues, we first used qRT-PCR to detect and compare the expression levels of 10 lncRNAs in CCA and adjacent tissues. Results showed that expressions of ENST00000601661.1, NR_003051 and ENST00000516869.1 in CCA tissues were significantly higher than those in adjacent tissues compared to the other seven lncR-NAs (Figure 1, A1-A10).…”
Section: High Expression Of Rmrp Was Observed In Cca Tissues and Cementioning
confidence: 99%
See 1 more Smart Citation
“…Up‐regulation of an miR panel (i.e., 191, 486‐3p, 1274b, 16, 484) was described in bile EVs from patients with CCA compared to control individuals (i.e., patients with PSC, a known risk factor for CCA, biliary obstruction, or bile leak syndrome) with diagnostic significance (SEN, 67%; SPE, 96%) . In addition, two lncRNAs (ENST00000588480.1 and ENST00000517758.1) were reported up‐regulated in bile EVs from patients with CCA compared to biliary obstruction conditions (SEN, 83%; SPE, 59%; area under the receiver operating characteristic curve [AUROC], 0.709) …”
Section: Cholangiopathiesmentioning
confidence: 99%
“…These lncRNAs may promote proliferation, migration and invasion of CCA cells including lncRNA AFAP1-AS1, ASAP1-IT1, CCAT1, CCAT2, H19, HULC, LINC01296, ENST0000058480.1, ENST00000517758.1, MALAT1, NEAT1, PANDAR, SNHG1, Sox2ot, SPRY4-IT1, TP73-AS1 etc. [23,29,30,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. In ICC, LncRNA CPS1-IT1 and TLINC are highly expressed [33,50].…”
Section: Lncrna Promotes Cca Proliferation Migration and Invasionmentioning
confidence: 99%